Adidas vs. Puma : a long-running rivalry - Abdo, Kenny, 1986- (Minneapolis, MN : Fly! an imprint of Abdo Zoom, 2023)
This title focuses on the feud between the companies Adidas and Puma while offering information related to their histories, combative relationships, and the legacies they leave behind. This hi-lo title includes photographs, simple text, glossary, and an index. Aligned to Common Core Standards and correlated to state standards.
Includes index.
Keywords: Adidas AG -- Juvenile literature; PUMA AG Rudolf Dassler Sport -- Juvenile literature; Sport clothes industry -- Juvenile literature; Athletic shoes -- Juvenile literature; Competition -- Juvenile literature